Radiolabeling and Bio-distribution study of ICD-85 with Technetium-99m as a cancer treatment agent in mice - Shirmardi, Seyed Pezhman; Erfani, Mostafa; Zare, Abbas; Mirzaei, Hamidreza; Mola, Masoud (Archives of Advances in Biosciences, 2018)
ICD-85 is a combination of three poly-peptides, ranging from 10,000 to 30,000 Dalton, derived from the venoms of an Iranian brown snake (Agkistrodon halys) and a yellow scorpion (Hemiscorpius lepturus). Labeling of this ICD-85 was successfully achieved with 99mTc, through direct method using SnF2 as reducing agent. Labeled ICD-85 was injected into mice to determine the excretion pathway. The results show that the maximum labeling yield (>75%) was obtained by using 30 μg of ICD-85 in phosphate buffer (60 μl, pH 7.1) at room temperature. Bio-distribution studies with radiolabeled ICD-85 shows moderate clearance of the complex from blood. The improvement of the immunotherapeutic treatment of cancer requires a better knowledge of the biological actions of the ICD-85 since tissue distribution studies are very important for clinical purpose.